ANALISIS MODUL BELAJAR PESERTA DIDIK LITERASI NUMERASI KELAS IV DITINJAU DARI ASPEK KESESUAIAN DENGAN KURIKULUM MERDEKA - Ika Sukamto Putri, Marcela; Trimurtini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the suitability of teaching materials with the curriculum and the suitability of the material with the types of questions given. Changes in the curriculum lead to changes in teaching materials. The method used in this research is qualitative document study. Based on the results of the study it can be concluded that; the suitability of teaching materials with the curriculum is stated to be in accordance, but in the textbook there are several incompatibilities, including (1) the absence of CP and TP in each chapter; (2) incompatibility of CP, TP with existing chapters; (3) incompatibility of material with questions. This suitability is the goal so that the learning outcomes of students can be carried out properly and students can get material that is appropriate to the level and able to improve students' abilities.